yap1b, a divergent Yap/Taz family member, cooperates with yap1 in survival and morphogenesis via common transcriptional targets - Vázquez-Marín, Javier; Gutiérrez Triana, José Arturo; Almuedo-Castillo, María; Buono, Lorena; Gómez-Skarmeta, José Luis; Mateo, Juan L.; Wittbrodt, Joachim; Martínez-Morales, Juan Ramón (Development, 2019)
Skip to Next Section - Yap1/Taz are well-known Hippo effectors triggering complex transcriptional programs controlling growth, survival and cancer progression. Here, we describe yap1b, a new Yap1/Taz family member with a unique transcriptional activation domain that cannot be phosphorylated by Src/Yes kinases. We show that yap1b evolved specifically in euteleosts (i.e. including medaka but not zebrafish) by duplication and adaptation of yap1. Using DamID-seq, we generated maps of chromatin occupancy for Yap1, Taz (Wwtr1) and Yap1b in gastrulating zebrafish and medaka embryos. Our comparative analyses uncover the genetic programs controlled by Yap family proteins during early embryogenesis, and show largely overlapping targets for Yap1 and Yap1b. CRISPR/Cas9-induced mutation of yap1b in medaka does not result in an overt phenotype during embryogenesis or adulthood. However, yap1b mutation strongly enhances the embryonic malformations observed in yap1 mutants. Thus yap1−/−; yap1b−/− double mutants display more severe body flattening, eye misshaping and increased apoptosis than yap1−/− single mutants, thus revealing overlapping gene functions. Our results indicate that, despite its divergent transactivation domain, Yap1b cooperates with Yap1 to regulate cell survival and tissue morphogenesis during early development.
Gesehen am 17.04.2020